Speech intelligibility and recall of first and second language words heard at different signal-to-noise ratios - Hygge, Staffan; Kjellberg, Anders; Nöstl, Anatole (Frontiers in Psychology, 2015)
Free recall of spoken words in Swedish (native tongue) and English were assessed in two signal-to-noise ratio (SNR) conditions (+3 and +12 dB), with and without half of the heard words being repeated back orally directly after presentation (shadowing, speech intelligibility, (SI)). A total of 24 wordlists with 12 words each were presented in English and in Swedish to Swedish speaking college students. Pre-experimental measures of working memory capacity (OSPAN) were taken. A basic hypothesis was that the recall of the words would be impaired when the encoding of the words required more processing resources, thereby depleting working memory resources. This would be the case when the SNR was low or when the language was English. A low SNR was also expected to impair SI, but we wanted to compare the sizes of the SNR-effects on SI and recall. A low score on working memory capacity was expected to further add to the negative effects of SNR and Language on both SI and recall. The results indicated that SNR had strong effects on both SI and recall, but also that the effect size was larger for recall than for SI. Language had a main effect on recall, but not on SI. The shadowing procedure had different effects on recall of the early and late parts of the word lists. Working memory capacity was unimportant for the effect on SI and recall. Thus, recall appear to be a more sensitive indicator than SI for the acoustics of learning, which has implications for building codes and recommendations concerning classrooms and other workplaces where both hearing and learning is important.